That Religion in Which All Men Agree Freemasonry in American Culture. - Hackett, David G. (Berkeley : University of California Press, 2014)
This powerful study weaves the story of Freemasonry into the narrative of American religious history. Freighted with the mythical legacies of stonemasons' guilds and the Newtonian revolution, English Freemasonry arrived in colonial America with a vast array of cultural baggage, which was drawn on, added to, and transformed during its sojourn through American culture. David G. Hackett argues that from the 1730s through the early twentieth century the religious worlds of an evolving American social order broadly appropriated the beliefs and initiatory practices of this all-male society. For much.
8. Jews and Catholics, 1723-1920Epilogue; Notes; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y; Z
Description based upon print version of record.
Keywords: Freemasonry -- United States -- History; Freemasons -- United States -- History; Freemasonry -- United States -- History; Group identity -- United States -- History; United States -- Religion -- History; SOCIAL SCIENCE / General; Electronic books